Measurement of the production cross-section of $$J/\psi $$ J/ψ and $$\psi (2{\textrm{S}})$$ ψ(2S) mesons in pp collisions at $$\sqrt{s} = 13$$ s=13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2024)
Springer Open.